Analisis Perbandingan Perilaku Keuangan Mahasiswa Penerima Dan Non Penerima Beasiswa Pada Mahasiswa Universitas Teuku Umar Prodi Manajemen - Cut Fiya Salfani (INDO PUBLISHING, 2026)
This study aims to analyze the differences in financial behavior between scholarship recipient students and non-scholarship recipient students in the Management Study Program at Teuku Umar University. This research employed a quantitative approach with a comparative design. The population consisted of 509 students from the 2021 to 2024 cohorts, while the sample comprised 84 respondents, consisting of 42 scholarship recipients and 42 non-scholarship recipients. The sampling technique used was purposive sampling, and the data were collected through questionnaires. Data analysis was conducted using the Mann-Whitney Test. The results indicate a significant difference in financial behavior between scholarship recipients and non-scholarship recipients, with an Asymp. Sig. (2-tailed) value of 0.004 < 0.05. These findings suggest that scholarship status influences students’ financial behavior. Specifically, scholarship recipients tend to be more organized and disciplined in managing their finances compared to non-scholarship recipients.